Instagram as a knowledge mobilization platform for youth resilience research: An exploratory study - Vakili, Negar; Stewart, Sherry H; Smith, Savanah; Mathew, Annphin; Wekerle, Christine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2020)
Objectives: Social media (SoMe) is globally prevalent, but its relevance for disseminating sensitive topics, such as violence victimization and mental health among adolescents and emerging adults, remain under-researched. Youth-dominate platforms may be well-suited for resilience messaging on safety, health, and well-being, and exploratory knowledge mobilization research. Research from a common team funding source supported a secondary objective that thematically linked research could be used to impact dissemination. Methods: This experiment utilized an ABA design, with a two-week baseline, followed by SoMe posting on weeks "A" and no posting on weeks "B" from a single Instagram account. During posting weeks, image-based messages from nine open access articles, from a risk and resilience research team, were posted three times per day. Each post contained a link to the associated open-access research article. Outcome dissemination indices, collected weekly, were reads of the referenced articles on a research-based networking site, ResearchGate. Results: Instagram indices formed the basis of our manipulation check. Relative to periods of inactivity, periods of active Instagram engagement led to significant increases in the number of Instagram impressions, website clicks, and followers, and in the number of reads of the posted ResearchGate articles. Implications: As the first study to examine Instagram impact for risk and resilience research, these findings encourage further SoMe work in this area of high public health import.